Mentoring as Correlate of Self Confidence and Job Satisfaction: A Psychological Perspective - Foluke, Siwoku-Awi Omotayo (Human Resource and Leadership Journal, 2020)
Purpose: This article developed from a presentation at the national Conference of Nigerian Psychological Association which took place at the Ile-Ife under the auspices of IfePsychologia Centre, Department of Psychology, Obafemi Awolowo University in 2014. The theme of the conference was on mentoring and development. Consequently, this research paper was aimed at portraying how mentoring mediates in human development as it may lead to job satisfaction and enhanced output. Methodology: An instrument called "Inventory on Mentoring as Correlate of Self-Confidence and Job Satisfaction was used to gather data which was analysed and interpreted, using the arithmetic percentage to calculate the differences in the number of respondents and their implications in job performance. Results: This study has proved that the art of mentoring is inherent in counselling psychology, personnel psychology and human development; this makes the mentor a counsellor, a consultant and a cheerleader, who provides support and enthusiasm for his/her team. S/He provides guidance based on experience and s/he demonstrates problem solving qualities and helps the mentee uncover his/her hidden potential. There is no doubt that mentoring can improve an individual's job performance and satisfaction since the output is enhanced; nevertheless, a worker that is not self-motivated and has a disposition that undermines the learning process may not benefit much from the process. The mentor at a place of work who wants to maximise effort for optimal outcomes may drive hard on the mentee. Unique contribution to theory, practice and policy: It is recommended that teachers and other facilitators should undergo training in mentoring so that they can better handle the learners. There should be better interrelationship and team spirit when the cheerleader, the mentor is given the room to make an impact. In government, new politicians should be properly mentored by the older ones on the jobs that there can be continuity and projects will be accomplished without rancour or ethnic prejudices as in African countries. In particular, the police force, security operative's road safety officers should be properly mentored so that they are not sadists who desire to impose on people without a rational justification for doing so.